A series of silver(i) coordination polymers of a new linear 4-((pyridin-4-ylthio)methyl)pyridine ligand: the role of organic and inorganic anions. Issue 4 (2nd December 2014) - Wan, Chong-Qing; Sun, Xiao-Li; Li, Ai-Min; Sun, Xin-Zhan; Lee, Hung Kay; Han, Hong-Liang; Che, Guang-Bo
Abstract : Systemic investigation of various counter anions' effect on coordination assembly of ten Ag I complexes with the new linear ligand PTMP. Abstract : Ten silver(i ) coordination polymers [Ag2 (PTMP)2 (L1)2 ]·3H2 O∞ (1 ), [Ag2 (PTMP)2 (L2)]·7H2 O∞ (2 ), [Ag2 (PTMP)2 (L3)]·2CH3 OH∞ (3 ), [Ag2 (PTMP)2 (L4)]·5H2 O∞ (4 ), [Ag(PTMP)]·0.5(L5)·2H2 O∞ (5 ), [Ag(PTMP)(L6)0.5 ]·H2 O∞ (6 ), [Ag3 (PTMP)3 (L7)]·2.25H2 O∞ (7 ), [Ag(PTMP)(NO3 )]∞ (8 ), [Ag(PTMP)]·(BF4 )∞ (9 ) and [Ag(PTMP)]·(CF3 SO3 )·0.5H2 O∞ (10 ) derived from a new flexible 4-((pyridin-4-ylthio)methyl)pyridine ligand (abbreviated as PTMP) have been synthesized and fully characterized (L1 = pentafluoropropionate, L2 = malonate, L3 = 2, 2, 3, 3, 4, 4-hexafluoropentanedioate, L4 = 1, 4-cyclohexanedicarboxylate, L5 = 1, 4-benzenedicarboxylate, L6 = 1, 1′-biphenyl-4, 4′-dicarboxylate and L7 = 2-hydroxypropane-1, 2, 3-tricarboxylate). These coordination polymers exhibit fascinating 1-D chains and 2-D and 3-D network structures with the PTMP functioning as a linear building block. Under a solvent medium with small van der Waals volume, the tuning effect of various anions from monocarboxylate to polycarboxylate (L1–L7) and the inorganic NO3 −, BF4 − and CF3 SO3 − on the construction of complexes1–10 have been systematically investigated and discussed.